2017
DOI: 10.1136/annrheumdis-2017-212603
|View full text |Cite|
|
Sign up to set email alerts
|

Stratification of knee osteoarthritis: two major patient subgroups identified by genome-wide expression analysis of articular cartilage

Abstract: IntroductionOsteoarthritis (OA) is a heterogeneous and complex disease. We have used a network biology approach based on genome-wide analysis of gene expression in OA knee cartilage to seek evidence for pathogenic mechanisms that may distinguish different patient subgroups.MethodsResults from RNA-Sequencing (RNA-Seq) were collected from intact knee cartilage at total knee replacement from 44 patients with OA, from 16 additional patients with OA and 10 control patients with non-OA. Results were analysed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(78 citation statements)
references
References 48 publications
5
71
1
1
Order By: Relevance
“…These add to traditional histochemistry-based approaches and offer the possibility of a new disease taxonomy. Bulk genome-wide expression analysis of chondrocytes in articular cartilage revealed two major patient subgroups, differing in complement activation, innate immune responses, and Wnt and TGFβ signaling response [ 83 •]. Single-cell sequencing has also identified cell subsets associated with both cartilage zone and level of damage [ 84 ••].…”
Section: Disease Stratification—breaking Down a Spectrum Of Diseases mentioning
confidence: 99%
“…These add to traditional histochemistry-based approaches and offer the possibility of a new disease taxonomy. Bulk genome-wide expression analysis of chondrocytes in articular cartilage revealed two major patient subgroups, differing in complement activation, innate immune responses, and Wnt and TGFβ signaling response [ 83 •]. Single-cell sequencing has also identified cell subsets associated with both cartilage zone and level of damage [ 84 ••].…”
Section: Disease Stratification—breaking Down a Spectrum Of Diseases mentioning
confidence: 99%
“…To validate the 7-gene classifier, we obtained an independent gene expression dataset of low-grade cartilage samples from 60 knee osteoarthritis patients undergoing joint replacement surgery 11 . The samples had been assigned into two groups, reflecting differences in complement activation and innate immunity.…”
Section: -Gene Classifier Predicts Clusteringmentioning
confidence: 99%
“…We obtained RNA expression data from low-grade cartilage tissue of 60 knee osteoarthritis patients undergoing joint replacement (27 women, 33 men, age range 63-85 years), sequenced on Illumina HiSeq 2500, with transcript quantification using kallisto and quality control as described previously 11 . We obtained gene-level data and removed batch effects as for the discovery data (Supplementary Methods).…”
Section: Replication Of Clustering Classifiermentioning
confidence: 99%
“…However, there is a clear positive correlation between synovial inflammation and clinical features of OA, such as pain, swelling, and cartilage damage (9)(10)(11)(12)(13)(14)(15). Recently, Soul et al (16) suggested that OA patients are heterogeneous and could be stratified into 2 major patient subgroups based on the gene expression of knee articular cartilage, showing altered patterns of matrix protein gene expression (16). Indeed, clinical heterogeneity in OA pathogenesis is increasingly becoming recognized (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%